2022
DOI: 10.1001/jamapediatrics.2022.1110
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Upper Airway Disease in Children With the Omicron (B.1.1.529) Variant of SARS-CoV-2—A Report From the US National COVID Cohort Collaborative

Abstract: This cohort study uses data from the US National COVID Cohort Collaborative to evaluate upper airway infections in children during the surge of the Omicron (B.1.1.529) variant of SARS-CoV-2 in the US.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
44
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 4 publications
7
44
1
Order By: Relevance
“…This can be seen by comparing the percentage of patients aged 0-3 years in our data with that of the reported symptomatic patients aged 0-5 years in China from January 16, 2020 to February 8, 2020 [70.3% aged 0-3 vs. 41.4% (845/2039) aged 0-5 years] [1]. This finding is consistent with the latest published paper demonstrating that the average age of hospitalized pediatric cases during the Omicron period was much lower than that in the pre-Omicron period (2.2 ± 2.1 vs. 4.4 ± 4.5 years, P < 0.001) [2]. The potential reasons for such a situation are that vaccination of children aged 3-17 years was initiated on Nov. 2021 and that students aged 3-17 years had shifted to online learning since March 12, 2022 in Shanghai prevented COVID-19 transmission among them in schools.…”
supporting
confidence: 85%
“…This can be seen by comparing the percentage of patients aged 0-3 years in our data with that of the reported symptomatic patients aged 0-5 years in China from January 16, 2020 to February 8, 2020 [70.3% aged 0-3 vs. 41.4% (845/2039) aged 0-5 years] [1]. This finding is consistent with the latest published paper demonstrating that the average age of hospitalized pediatric cases during the Omicron period was much lower than that in the pre-Omicron period (2.2 ± 2.1 vs. 4.4 ± 4.5 years, P < 0.001) [2]. The potential reasons for such a situation are that vaccination of children aged 3-17 years was initiated on Nov. 2021 and that students aged 3-17 years had shifted to online learning since March 12, 2022 in Shanghai prevented COVID-19 transmission among them in schools.…”
supporting
confidence: 85%
“…The results of this cross-sectional study expand on recent single-center studies 1 , 2 showing that hospitalizations for COVID-19–related croup increased after the onset of the Omicron variant. A more recent national investigation 3 found that the percentage of children diagnosed with SARS-CoV-2 hospitalized with upper-airway infections increased significantly from pre-Omicron (1.4%) compared with Omicron (4.1%) periods. The hospitalization rate was higher in our study, which may be associated with use of ICD-10 codes rather than positive SARS-CoV-2 test results for COVID-19 data.…”
Section: Discussionmentioning
confidence: 98%
“…Recent reports have found an association between SARS-CoV-2 and croup. 1 , 2 , 3 We aimed to investigate whether SARS-CoV-2 variants were associated with the proportion of children with croup, as well as hospital and intensive care unit (ICU) admissions and racemic epinephrine (RE) treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicated the Omicron variant seemed to be 'friendly' to children with the PCR conversion interval of 8 days and mild symptoms even without any antiviral drugs. As already known, young children are especially vulnerable to have upper airway infection due to their relatively narrow and collapsible nasal passages, and that babies breathe only through their noses (32), which means the virus mainly lingers in the upper respiratory tract. But at the same time, the virus can be relatively driven out by breathing or coughing.…”
Section: Discussionmentioning
confidence: 99%